Al Wakalah and its impact on the growth and performance of Takaful companies: a Malaysian case - Annuar, Hairul Azlan; Rosly, Saiful Azhar; Abdul Rashid, Hafiz Majdi (European Center for Peace and Development of the University for Peace, 2004)
Marketing Islamic insurance (takaful) products does not imply exploiting the religious factor alone. Equally important is the marketing channel. As a marketing tool the agency system is vital. Insurance agents who sell policies are not employees of insurance companies. They work on a commission basis and thus are motivated by the volume of sales made. By using agents, insurance companies can cut overhead costs and help expand markets without using or setting up new costly subsidiaries. The first takaful company in Malaysia, Syarikat Takaful Malaysia Berhad (STMB), does not use the agency system (al wakalah), in contrast to the second company, Takaful Nasional Sendirian Berhad (TNSB). The different marketing channel used has a lot to do with both companies following different Islamic scholars’ views of the al wakalah contract. It centres upon differences in juristic interpretation (iktilaf) on whether the takaful company, as a manager (mudharib), can use part of the capital, in terms of premiums provided by the policyholders (rabulmal), to pay agents’ commissions. This study looks at how this difference in juristic views has impacted the performance of both takaful companies. The study found that TNSB performed better than STMB. In this sense, al wakalah is able to generate greater benefits (manfaat) than the takaful companies while not causing harm (madarrah)to the customers. It is therefore crucial for STMB to review its policy on al wakalah and embrace the system to improve its performance.